Trends in childhood injury mortality in Canada, 1979–2002. Issue 3 (2nd June 2006) - Pan, S Y; Ugnat, A-M; Semenciw, R; Desmeules, M; Mao, Y; MacLeod, M
Abstract : Objective: To examine national trends in mortality rates for injuries among Canadian children younger than 15 years in 1979–2002. Methods: Data on injury deaths were obtained from the Canadian Vital Statistics system at Statistics Canada. Injuries were classified using the codes for external cause of injury and poisoning (E-codes) by intent and by mechanism. Mortality rates were age adjusted to the 1990 world standard population. Negative binomial regression was used to estimate the secular trends. Results: Annual mortality rates for total and unintentional injuries declined substantially (from 23.8 and 21.7 in 1979 to 7.2 and 5.8 in 2002, respectively), whereas suicide deaths among children aged 10–14 showed an increasing trend. All Canadian provinces and territories showed a decreasing trend in mortality rates of total injuries. Motor vehicle related injuries were the most common cause of injury deaths (accounted for an average of 36.4% of total injury deaths), followed by suffocation (14.3%), drowning (13.5%), and burning (11.1%); however, suffocation was the leading cause for infants. The number of potential years of life lost due to injury before age 75 decreased from 89 343 in 1979 to 27 948 in 2002 for children aged 0–14 years. Conclusions: During the period 1979–2002, there were dramatic decreases in childhood mortality for total injuries and unintentional injuries as well as various degrees of reduction for all causes of injury except suffocation in children aged 10–14 years and drowning in infants. The reason for the reduction in injury mortality might be multifactoral.